2010
DOI: 10.1248/bpb.33.329
|View full text |Cite
|
Sign up to set email alerts
|

3,5-Di-<i>O</i>-caffeoyl-<i>epi</i>-quinic Acid from the Leaves and Stems of <i>Erigeron annuus</i> Inhibits Protein Glycation, Aldose Reductase, and Cataractogenesis

Abstract: In our ongoing project directed toward the discovery of novel treatments for diabetic complications from herbal medicines, sixteen compounds including three caffeoylquinic acids and four flavonoids were isolated from an EtOAc-soluble extract of the stems and leaves of Erigeron annuus. All the isolates were evaluated in vitro for inhibitory activity on the formation of advanced glycation end products (AGEs) and rat lens aldose reductase (RLAR). Of these, 3,5-di-O-caffeoyl-epi-quinic acid (3) exhibited the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 43 publications
(37 reference statements)
0
35
0
Order By: Relevance
“…Two caffeoyl erigerosides and a sucrose ester also were more effective AGEs inhibitors than AG. This is the first report on 3,5-di-O-caffeoyl-epi-quinic acid as an inhibitor of RLAR (rat lens aldose reductase), AGEs formation, AGEs-BSA cross-linking, and cataractogenesis [62].…”
Section: Cinnamic Acids and Derivativesmentioning
confidence: 84%
See 1 more Smart Citation
“…Two caffeoyl erigerosides and a sucrose ester also were more effective AGEs inhibitors than AG. This is the first report on 3,5-di-O-caffeoyl-epi-quinic acid as an inhibitor of RLAR (rat lens aldose reductase), AGEs formation, AGEs-BSA cross-linking, and cataractogenesis [62].…”
Section: Cinnamic Acids and Derivativesmentioning
confidence: 84%
“…The anti-glycation capacity of numerous medicinal herbs and dietary plants was comparable with [59], or even stronger than that of aminoguanidine [42,60,[61][62][63]. Several studies have demonstrated that the anti-glycation activity correlates significantly with the phenolic content of the tested plant extracts [5,50,59,64,65].…”
Section: Polyphenolsmentioning
confidence: 94%
“…Isolation of 3,5-diCQM 3,5-diCQM was isolated from the stems and leaves of Erigeron annuus [23] and its chemical structure was identified by comparing its physicochemical and spectral data with those in the literature [17]. In brief, air-dried stems and leaves of E. annuus (3.3 kg) were extracted with a total of 60 l MeOH (three times, 20 l each) at room temperature for 7 days, filtered, and concentrated to give a MeOH extract (330 g).…”
Section: Methodsmentioning
confidence: 99%
“…Nine standard compounds ( Figure 1 3,5-dicaffeoylquinic acid (H) and 4,5-dicaffeoylquinic acid (I)-were isolated from the leaves of Acanthopanax henryi and purified in our laboratory. Their purities were all determined to be over 95% using HPLC-DAD analysis, and their structures were elucidated by chemical and spectroscopic methods ( 1 H-NMR, 13 C-NMR, MS) in our previous study (11). HPLC-grade acetonitrile and methanol were purchased from Merck (Darmstadt, Germany), and all other chemicals were of analytical grade.…”
Section: Materials and Chemicalsmentioning
confidence: 99%